Study on Risk Assessment and Management of Landslide Hazard in New Bodong County, Three Gorge Reservoir - Wu, Yiping; Yin, Kunlong; Jiang, Wei (2009 International Conference on Management and Service Science, 2009)
In this paper, considering geological environment and landslide development in New Badong County, 11 representative factors are decided to assess landslide hazard in New Badong County. By using the Artificial Neural Network landslide hazard evaluating model and the advantages of GIS technology in image processing and space-analysis, landslide hazard zonation of New Badong County is compiled. The result of the assessment can be a gist and ensure for the land planning and the emigration project in Badong. And it provides professional base for the landslide hazard risk management of Badong. The risk management system, which is a combination of professional risk control and government decision-making risk management, is proposed. And in this system the preventive professional research, landslide hazard emergency plan, management functions of government and some other key processes are discussed. It provides ideas for the risk management of landslide hazard of Badong County. This system provides an effective way for the landslide hazard risk management of each district in the Reservoir of Three Gorge Project.